2014
DOI: 10.1016/j.neulet.2014.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Association of APOE polymorphisms and stressful life events with dementia in a Pakistani population

Abstract: Dementia is a major public health problem worldwide. Alzheimer’s disease (AD) is a major form of dementia and the APOE*4 allele is an established genetic risk factor for AD. Similarly, stressful life events are also associated with dementia. The objective of this study was to examine the association of APOE*4 and stressful life events with dementia in a Pakistani sample, which to our knowledge has not been reported previously. We also tested for an interaction between stressful life events and APOE*4 on dement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…To the best of our knowledge, this is the first study that has examined the association of APOE polymorphism with angiographically assessed stenosis and the number of diseased vessels among Pakistanis. The frequency of the APOE ∗ 4 allele in our sample was 11%, which is very similar to its reported frequency of 9% in a relatively older Pakistani control sample of 108 individuals [ 19 ] but slightly lower than the average frequency of 14% among Europeans [ 20 ].…”
Section: Discussionsupporting
confidence: 85%
“…To the best of our knowledge, this is the first study that has examined the association of APOE polymorphism with angiographically assessed stenosis and the number of diseased vessels among Pakistanis. The frequency of the APOE ∗ 4 allele in our sample was 11%, which is very similar to its reported frequency of 9% in a relatively older Pakistani control sample of 108 individuals [ 19 ] but slightly lower than the average frequency of 14% among Europeans [ 20 ].…”
Section: Discussionsupporting
confidence: 85%
“…Besides other risk factors, apolipoprotein E ( ApoE ) gene polymorphism has been implicated in predisposition to diabetes and dementia in old population, but the results from the different studies were inconclusive. However, in Pakistani population APO E4 alleles and ATP7B variant alleles are known genetic factors increasing the risk of AD [ 51 ], which is also corroborated with a the results of a large prospective cohort study confirmed case–control reports that women who are positive for the ε4 allele of the apolipoprotein E gene ( APOE ε4 ) are at greater risk of developing AD [ 52 ].…”
Section: Discussionmentioning
confidence: 58%
“…34 In more recent studies, the association between exposure to chronic stress and neurodegenerative disease was described. 35,36 The underlying mechanism of AD, one of the neurodegenerative diseases, in case of exposure to chronic stress, was a field of controversy. Anyway, studies on the discovery of drugs that can improve chronic stress-induced learning and memory impairments and neurodegeneration are of great importance for the treatment of AD.…”
Section: Discussionmentioning
confidence: 99%